2020
DOI: 10.1123/japa.2019-0070
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Whole-Body Vibration on Functional Mobility, Balance, Gait Strength, and Quality of Life in Institutionalized Older People: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: The aim of this study was to quantify the effect of whole-body vibration on balance, functional mobility, gait, functional performance, and quality of life in institutionalized older people. Eight databases were systematically reviewed, as recommended by the Cochrane Collaboration. This systematic review was designed to answer the acronym set by the participants, interventions, comparators, and outcomes (PICO)-model. Ten randomized controlled trials were included in the meta-analysis. The analysis of the mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…WBV Improve the Physical Function of Dialysis Patients Am J Nephrol 2023;54:35-41 DOI: 10.1159/000530219 is an alternative to traditional exercise; it is a safe, autonomous, and efficient way to increase or maintain muscle strength, functional mobility, and peripheral blood flow [28][29][30][31]. However, no significant improvement was found in terms of muscle mass, gait, and balance [32]. BFR training was demonstrated to mediate muscle hypertrophy to facilitate strength rehabilitation via the mechanisms of mechanical tension and metabolic stress [33].…”
Section: Discussionmentioning
confidence: 99%
“…WBV Improve the Physical Function of Dialysis Patients Am J Nephrol 2023;54:35-41 DOI: 10.1159/000530219 is an alternative to traditional exercise; it is a safe, autonomous, and efficient way to increase or maintain muscle strength, functional mobility, and peripheral blood flow [28][29][30][31]. However, no significant improvement was found in terms of muscle mass, gait, and balance [32]. BFR training was demonstrated to mediate muscle hypertrophy to facilitate strength rehabilitation via the mechanisms of mechanical tension and metabolic stress [33].…”
Section: Discussionmentioning
confidence: 99%
“…They were conducted by researchers affiliated with institutions in countries such as Austria, Australia, Canada, China, South Korea, Spain, the United States, and the United Kingdom. These meta-analyses analyzed a total of 235 studies conducted in various CS [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. The total number of participants was 56,241 with an average age range between 69 and 90 years.…”
Section: Resultsmentioning
confidence: 99%
“…Alvarez-Barbosa et al [35] Whole-body vibration improved functional mobility as assessed with the Time Up and Go test (MD = −2.49 s, 95% CI [−4.37, −0.61], p = 0.009).…”
Section: Schoberer Et Al [33]mentioning
confidence: 99%
“…It was concluded that combining strength training with WBV improved neuromuscular performance significantly more than strength training plus conventional balance training. Also, a recent systematic review and meta-analysis (10 studies including 557 subjects) summarized that WBV significantly improved functional mobility in elderly subjects [ 37 ]. It was hypothesized that these improvements could be useful for the tasks of daily living [ 37 ].…”
Section: Discussionmentioning
confidence: 99%